2020
DOI: 10.2147/cmar.s236576
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Long Noncoding RNA <em>FGD5-AS1</em> Acts as a Competing Endogenous RNA on microRNA-383 to Enhance the Malignant Characteristics of Esophageal Squamous Cell Carcinoma by Increasing SP1 Expression</p>

Abstract: These authors contributed equally to this workPurpose: Previous studies have identified the important roles of a long noncoding RNA called FGD5 antisense RNA 1 (FGD5-AS1) in several types of human cancer. Nonetheless, to our knowledge, the expression and functions of FGD5-AS1 in esophageal squamous cell carcinoma (ESCC) have not been clarified. In this study, we aimed to determine the expression status of long noncoding RNA FGD5-AS1 in ESCC, determine its participation in ESCC progression, and uncover the unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…FGD5-AS1 was aberrantly up-regulated in these tumors compared to adjacent normal tissues. Moreover, increased FGD5-AS1 expression manifested a close association with tumor size, TNM stage, and lymph node metastasis in esophageal squamous cell carcinoma 30 ; FGD5-AS1 may promote NSCLC cell proliferation 29 ; FGD5-AS1 knockdown inhibited colorectal cancer cell proliferation, migration, and invasion, and promoted cell apoptosis 27 . However, in this study, we found that FGD5-AS1 expression was significantly lower in ccRCC than in adjacent normal tissues, and increased FGD5-AS1 was associated with of longer OS and DFS.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…FGD5-AS1 was aberrantly up-regulated in these tumors compared to adjacent normal tissues. Moreover, increased FGD5-AS1 expression manifested a close association with tumor size, TNM stage, and lymph node metastasis in esophageal squamous cell carcinoma 30 ; FGD5-AS1 may promote NSCLC cell proliferation 29 ; FGD5-AS1 knockdown inhibited colorectal cancer cell proliferation, migration, and invasion, and promoted cell apoptosis 27 . However, in this study, we found that FGD5-AS1 expression was significantly lower in ccRCC than in adjacent normal tissues, and increased FGD5-AS1 was associated with of longer OS and DFS.…”
Section: Discussionmentioning
confidence: 98%
“…FGD5-AS1 was aberrantly up-regulated in these tumors compared to adjacent normal tissues. Moreover, increased FGD5-AS1 expression manifested a close association with tumor size, TNM stage, and lymph node metastasis in esophageal squamous cell carcinoma [30]; FGD5-AS1 may promote NSCLC cell proliferation [29];…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 What's more, high expression of FGD5-AS1 is associated with adverse clinicopathological parameters and short overall survival time of esophageal squamous cell carcinoma. 24 Similarly, overexpression of FGD5- AS1 enhances the proliferation of NSCLC cells. 11 Consistent with these researches, in the present work, FGD5-AS1 was experimentally proved to exhibit a cancer-promoting role in NSCLC: FGD5-AS1 expression was up-regulated in NSCLC tissues and cells, and its high expression in NSCLC tissues was associated with unfavorable pathological indexes; additionally, FGD5-AS1 knockdown impeded the proliferation, migration, invasion and EMT of NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, H1650 and A549 cells (5 Â 10 3 cells/well) were transferred into 96-well plates. At indicated times (12,24,48,72, and 96 h), 10 mL of CCK-8 solution was added into each well. After the cells were incubated for 2 h, a microplate reader (Bio-Rad, Hercules, CA, USA) was utilized for detection of absorbance of the cells in each well at 450 nm.…”
Section: Cell Counting Kit-8 (Cck-8) Assaymentioning
confidence: 99%